إجحاف قانون الأسرة في تنظيم حق الزيارة - قنيف, غنيمة (University of Eloued جامعة الوادي, 2022)
ضمن تقنين الأسرة الجزائري حق الزيارة كإحدى آثار الطلاق وتوابع الحضانة، إلا أنه كان شحيحا ومجحفا حين عدم تنظيمه لآليات ممارسة هذا الحق. الأمر الذي فتح المجال بمصرعيه لاجتهاد القضاء. وكذا لتعسف أصحاب حقي الحضانة والزيارة لغياب رادع قانوني. ليكون بذلك المحضون ضحية تصارع وانتقام الوالدين. لذلك يعد إعادة تنظيم هذا الحق قانونا وإثرائه موضوعا وأحكامًا وضوابطا، أمر ملح وضروري، إيقافًا لظاهرة تفكك الأسر وانحراف الأطفال. Abstract: Codification of the family ensured the visiting rights as one of the effects of divorce and the consequences of custody, but it was scarce and unfair as it did not regulate the mechanisms of exercising this right. Which opened the door to the jurisprudence, as well as the abuse of parents due to the absence of legal sanction, in a way that renders the child in custody a victim of parental struggle and revenge, and a means to carry out legally prohibited actions. Therefore, reregulating this right and enriching it in subject, provisions and regulations, is urgent and necessary to stop the phenomenon of family breakdown and juvenile delinquency.
Inequality of F amily L aw in V isitation P lanning
مقال
Keywords: إجحاف ; الزيارة ; تسليم الطفل ; خطف ; آليات ; المحض ; ن ; قيد ; الطلاق ; الحضانة; Unfairness; law; regulation; mechanisms; visiting; delivery of the child in custody; restriction; divorce; kidnapping.